Cardiotoxicity is mitigated after a supervised exercise program in HER2-positive breast cancer undergoing adjuvant trastuzumab - Jacquinot, Quentin; Meneveau, Nathalie; Falcoz, Antoine; Bouhaddi, Malika; Roux, Pauline; Degano, Bruno; Chatot, Marion; Curtit, Elsa; Mansi, Laura; Paillard, Marie-Justine; Bazan, Fernando; Chaigneau, Loïc; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Trastuzumab is used, alone or in conjunction with standard chemotherapy, to treat HER2-positive breast cancer (BC). Although it improves cancer outcomes, trastuzumab. can lead to cardiotoxicity. Physical exercise is a safe and effective supportive therapy in the management of side effects, but the cardioprotective effects of exercise are still unclear. Objectives The primary aim of this study was to test whether trastuzumab-induced cardiotoxicity [left ventricular ejection fraction (LVEF) under 50%, or an absolute drop in LVEF of 10%] was reduced after a supervised exercise program of 3 months in patients with HER2-positive breast cancer. Secondary endpoints were to evaluate (i) cardiotoxicity rates using other criteria, (ii) cardiac parameters, (iii) cardiorespiratory fitness and (iv) whether a change in LVEF influences the cardiorespiratory fitness. Methods 89 women were randomized to receive adjuvant trastuzumab in combination with a training program (training group: TG; n = 46) or trastuzumab alone (control group: CG; n = 43). The primary and secondary endpoints were evaluated at the end of the supervised exercise program of 3 months (T3). Results After exercise program, 90.5 % of TG patients and 81.8% of CG patients did not exhibit cardiotoxicity. Furthermore, whatever the used criterion, percentage of patients without cardiotoxicity were greater in TG (97.6 and 100% respectively) than in CG (90.9 and 93.9% respectively). LVEF and GLS values remained stable in both groups without any difference between the groups. In contrast, at T3, peak VO2 (+2.6 mL.min−1.kg−1; 95%CI, 1.8 to 3.4) and maximal power (+21.3 W; 95%CI, 17.3 to 25.3) increased significantly in TG, whereas they were unchanged in CG (peak VO2: +0.2 mL.min−1.kg−1; 95%CI, −0.5 to 0.9 and maximal power: +0.7 W, 95%CI, −3.6 to 5.1) compared to values measured at T0. No correlation between LVEF changes and peak VO2 or maximal power was observed. Conclusion A 12-week supervised exercise regimen was safe and improved the cardiopulmonary fitness in particular peak VO2, in HER2-positive BC patients treated with adjuvant trastuzumab therapy. The study is under powered to come to any conclusion regarding the effect on cardiotoxicity. Clinical trial registration www.ClinicalTrials.gov, identifier: NCT02433067.